The role of topical gel containing chitosan, 0.2% chlorhexidine, allantoin and dexpanthenol on the wound healing after surgical extraction of impacted mandibular third molar - Chauhan, Pranshu; Laskar, Shyamalendu; Meena, Shakti Singh; Singh, Mamta; Suman, Anshika (International journal of health sciences, 2022)
Odontostomologic procedures like extractions especially surgical removal of impacted 3rd molars, implants, biopsies etc are often associated with post-operative pain and inflammation. Traditionally chlorhexidine was used in this regard. Recently, topical gel, Bexident Post (ISDIN, SPAIN) has been in use to control post-operative discomfort. The aim of this study is to clinically evaluate the efficacy of Bexident Post (ISDIN, SPAIN) that contains chitosan, dexpenthanol, allantoin and 0.2% chlorhexidine on wound healing after surgical extraction of mandibular impacted 3rd molars. A study sample of 10 patients with similar type of bilateral impacted mandibular 3rd molar was included in the study. Total of 10 extractions were assingned in one of the two groups. Only difference between the two sides in terms of surgical protocol will be the Experimental side applied 10 mL thrice daily for 10 days while Control side did not. All patients were aware of the purpose of present study and written consent was taken requiring their participation. Results showed that facial swelling, mouth opening and pain were all significant between the two groups. The groups were homogenous only in terms of infection as neither of the groups showed post-operative signs of infection.